Answer:
Part 41) The solution of the compound inequality is equal to the interval [-1.5,-0.5)
Part 45) The solution of the compound inequality is equal to the interval
(-∞, -0.5] ∪ [1,∞)
Step-by-step explanation:
Part 41) we have
![-4\leq 2+4x < 0](https://tex.z-dn.net/?f=-4%5Cleq%202%2B4x%20%3C%200)
Divide the compound inequality into two inequalities
-----> inequality A
Solve for x
Subtract 2 both sides
![-4-2\leq 4x](https://tex.z-dn.net/?f=-4-2%5Cleq%204x%20)
![-6\leq 4x](https://tex.z-dn.net/?f=-6%5Cleq%204x%20)
Divide by 4 both sides
![-1.5\leq x](https://tex.z-dn.net/?f=-1.5%5Cleq%20x%20)
Rewrite
![x\geq -1.5](https://tex.z-dn.net/?f=x%5Cgeq%20-1.5)
The solution of the inequality A is the interval -----> [-1.5,∞)
-----> inequality B
Solve for x
Subtract 2 both sides
Divide by 4 both sides
The solution of the inequality B is the interval ------> (-∞, -0.5)
The solution of the inequality A and the Inequality B is equal to
[-1.5,∞)∩ (-∞, -0.5)------> [-1.5,-0.5)
see the attached figure N 1
Part 45) we have
or ![3x+1\geq 4](https://tex.z-dn.net/?f=3x%2B1%5Cgeq%204)
Solve the inequality A
![2x-3\leq -4](https://tex.z-dn.net/?f=2x-3%5Cleq%20-4)
Adds 3 both sides
![2x\leq -4+3](https://tex.z-dn.net/?f=2x%5Cleq%20-4%2B3)
![2x\leq -1](https://tex.z-dn.net/?f=2x%5Cleq%20-1)
Divide by 2 both sides
![x\leq -0.5](https://tex.z-dn.net/?f=x%5Cleq%20-0.5)
The solution of the inequality A is the interval ------> (-∞, -0.5]
Solve the inequality B
![3x+1\geq 4](https://tex.z-dn.net/?f=3x%2B1%5Cgeq%204)
Subtract 1 both sides
![3x\geq 4-1](https://tex.z-dn.net/?f=3x%5Cgeq%204-1)
![3x\geq 3](https://tex.z-dn.net/?f=3x%5Cgeq%203)
Divide by 3 both sides
![x\geq 1](https://tex.z-dn.net/?f=x%5Cgeq%201)
The solution of the inequality B is the interval -----> [1,∞)
The solution of the compound inequality is equal to
(-∞, -0.5] ∪ [1,∞)
see the attached figure N 2